Comprehensive medicinal chemistry survey highlights a portfolio of lead molecules for Alzheimer’s disease therapy - Bhansali, Pravin R.; Sonkusare, Shashank M.; Savale, Shubhangi S.; Wijayasinghe, Yasanandana S.; Liao, Yini; Sloan, Douglas C.; Chaturbhuj, Ganesh U.; Muntean, Brian S. (Frontiers in Chemistry, 2025)
The World Health Organization reports 10 million new patients with dementia each year. The most common form of dementia is Alzheimer’s disease (AD), which constitutes up to 70% of cases. AD is mainly characterized by loss of memory, which, in addition to its debilitating individual effect, represents a burden of 1.3 trillion US dollars globally. The staggering scale of hardship has spurred intense investigations from the scientific community in search of therapeutic solutions. Recent advances to combat AD involve the identification of numerous neural targets and concomitant chemical interventions as nodes of therapy. Due to disparate biological and chemical facets of AD therapy, a comprehensive perspective covering both arenas is currently missing from the literature. This perspective aims to provide an extensive understanding of anti-AD mechanics alongside small-molecule drug design efforts from a medicinal chemist viewpoint. We are confident that this survey of the literature will provide a resourceful motivation to propel future research efforts towards successful Alzheimer’s disease therapy.